PENGARUH PENDEKATAN QUANTUM TEACHING TERHADAP PEROLEHAN BELAJAR TEMATIK KELAS V SDN 03 PONTIANAK SELATAN - Iwastie, Junny; Marzuki, Marzuki; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "How  is The effect of Quantum Teaching Approach on Students’ Learning Outcome in Thematic of 5th Grade Students of Sekolah Dasar Negeri 03 Pontianak Selatan?".  This research uses Pre-Experimental Research Design, the type of One Group Pretest-Posttest Design. The researcher took the samples by using purposive sampling, so that the sample of this research was 34 students in 5th Grade D. The technique used in data collection was measurement with data collection tools in the form of multiple choice tests. Based on the results of the research, mean values of pre-test and post-test were 69.32 and 77.15. After t test was obtained tcount 7.97 while t table with db = 34-1 = 33 and significant level (α) = 5% was 2.042, which means 7.97 ≥ 2.042, there were tcount> ttable significantly different and Ha was accepted. From the results of the calculation of the effect size, obtained of 0.56 with the criteria being. In conclusions, the quantum teaching approach contributes 50% or 0.5 to thematic learning 5th Grade Students of Sekolah Dasar Negeri 03 Pontianak Selatan. Keywords: Effect, Quantum Teaching Approach,Students’ Learning Outcome             InThe Thematic Lesson.